Mesenteric extraskeletal osteosarcoma with telangiectatic features: a case report - Lee, Kyung Hwa (BioMed Central, 2007)
BACKGROUND: Extraskeletal osteosarcoma is a rare malignant mesenchymal tumor, with a predominant occurrence in the extremities. Only two cases of mesenteric extraskeletal osteosarcoma have been documented. We describe an unusual case of extraskeletal osteosarcoma with telangiectatic features occurring in the mesentery. CASE PRESENTATION: A 67-year-old male presented with blood-tinged stool of 1-month's duration. On colonoscopy, a solid mass was detected protruding from the colon wall. Computed tomography showed a 15 × 9.7 cm heterogeneously enhancing mass, with mottled calcification and a cystic portion, occupying the left upper quadrant of the abdominal cavity. Curative resection of the tumor was performed, and the excised tumor was composed of large multilocular cysts containing old hematomas and necrotic debris. The histology revealed an osteosarcoma showing osteoid formation and blood-filled spaces lined with atypical cells. Despite postoperative chemotherapy, he developed a recurrent peritoneal mass and multiple lung metastases 3 months postoperatively. CONCLUSION: Given the rarity of cases of mesenteric extraskeletal osteosarcoma, its biologic behavior at this location remains to be determined. However, extraskeletal osteosarcoma with telangiectatic features is an uncommon entity to be recognized because of the possible fatal outcome related to the tumors.